The Correlation of Body Composition with Random Blood Glucose in Young Adult Medical Students at Pelita Harapan University - Siregar, Rohana UP; Wijaya, Anggelia; Kartono, William S; Fernhandho, Vether; Christy, Grace A; Atmadja, Wahyuni L (Universitas Kristen Maranatha, 2025)
Body composition refers to the arrangement of fat, water, bone, muscle, skin, and other lean tissues that constitute the body. A shift in composition of the body, increased fat storage and reduced muscle mass lead to metabolic imbalance and elevate the likelihood of type 2 diabetes.Although the previous studies have shown the alterations in body composition related to their age, the correlation of body composition to random blood glucose of young adults has not yet been explored clearly. Therefore, our goal is to establish the relationship between body fat, muscle mass, and random blood glucose levels in young adults. In this cross-sectional study, 296 medical students aged 19-24 years old were included and examined for their body composition with Bioelectrical Impedance Analysis and measured random blood glucose with a glucometer. Using Spearman's correlation (p<0.05), we found significant positive correlations for body fat (r=0.133, p=0.022) and fat-to-muscle ratio (r=0.131, p=0.024), whereas muscle mass exhibited an inverse relationship (r=-0.130, p=0.026). Based on gender, the correlation for body composition and random blood glucose were significant in males but not for females. Higher body fat and lower muscle mass are associated with elevated random blood glucose levels in young adults, particularly in males.